Copper-substituted forms of the wild type and C42A variant of rubredoxin - Thapper, Anders (2013)
In order to gain insights into the interplay between Cu(I) and Cu(II) in sulfur-rich protein environments, the first preparation and characterization of copper-substituted forms of the wild-type rubredoxin (Rd) from Desulfovibrio vulgaris Hildenborough are reported, as well as those of its variant C42A-Rd. The initial products appear to be tetrahedral CuI(S–Cys)n species for the wild type (n = 4) and the variant C42A (n = 3, with an additional unidentified ligand). These species are unstable to aerial oxidation to products, whose properties are consistent with square planar CuII(S–Cys)n species. These Cu(II) intermediates are susceptible to auto-reduction by ligand S–Cys to produce stable Cu(I) final products. The original Cu(I) center in the wild-type system can be regenerated by reduction, suggesting that the active site can accommodate CuI(S–Cys)2 and Cys–S–S–Cys fragments in the final product. The absence of one S–Cys ligand prevents similar regeneration in the C42A–Rd system. These results emphasize the redox instability of CuII–(S–Cys)n centers.